2010
DOI: 10.1258/mi.2010.010022
|View full text |Cite
|
Sign up to set email alerts
|

The age of ovarian failure following premenopausal hysterectomy with ovarian conservation

Abstract: This is the largest number of cases collected prospectively looking at ovarian failure after hysterectomy. Earlier ovarian failure occurred in those women having unilateral oophorectomy or vaginal hysterectomy. Early ovarian failure was not confirmed across the study group with only 2% of women having confirmed ovarian failure by Kaplan-Meier estimate one year after surgery and 14% at five years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
0
10
1
4
Order By: Relevance
“…However, because these studies either had no control group (19) or compared women with hysterectomy to women with uterine artery embolization (21, 22), the results are not strictly comparable to our study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…However, because these studies either had no control group (19) or compared women with hysterectomy to women with uterine artery embolization (21, 22), the results are not strictly comparable to our study.…”
Section: Discussioncontrasting
confidence: 81%
“…Other recent studies that have examined risk of ovarian failure after hysterectomy have been inconsistent in their conclusions, with two studies reporting no effect (19, 21) while another reported an adverse effect of hysterectomy on ovarian function (22). However, because these studies either had no control group (19) or compared women with hysterectomy to women with uterine artery embolization (21, 22), the results are not strictly comparable to our study.…”
Section: Discussionmentioning
confidence: 98%
“…Some evidence also suggests that women who undergo a USO have impaired ovarian function and earlier menopause following surgery [15][16][17][18] compared with women who maintain both ovaries. Thus, women surveyed remote from fertility-sparing USO may be menopausal and would have similar levels of sexual satisfaction as women who underwent a full BSO.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Surgeries, especially those in pelvic region, such as hysterectomy [96], may also cause POI by affecting blood supply to ovaries or causing local inflammation [97]. Laparoscopic ovarian drilling (LOD) in women with PCOS does not necessarily end in diminished ovarian reserve or POI according to existing literature [98].…”
Section: Iatrogenic Causesmentioning
confidence: 99%